miR-3940-5p reduces amyloid β production via selectively targeting PSEN1 - Qi, Yanmei; Wang, Xu; Guo, Xihan (Frontiers in Aging Neuroscience, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by the accumulation of amyloid beta (Aβ) in brain. Mounting evidence has revealed critical roles of microRNAs (miRNAs) in AD pathogenesis; however, the miRNAs directly targeting presenilin1 (PSEN1), which encodes the catalytic core subunit of γ-secretase that limits the production of Aβ from amyloid precursor protein (APP), are extremely understudied. The present study aimed to identify miRNAs targeting PSEN1 and its effect on Aβ production. This study first predicted 5 candidate miRNAs that may target PSEN1,through websites such as TargetScan, miRDB, and miRwalk. Subsequently, the targeting specificity of the candidate miRNAs towards PS1 was validated using dual-luciferase reporter assays. To investigate the regulatory effect of miR-3940-5p on gene expression based on its targeting of PS1, miR-3940-5p mimics or inhibitors were transiently transfected into SH-SY5Y cells. Changes in PSEN1 transcription and translation in the tested cells were detected using RT-qPCR and Western Blot, respectively. Finally, to explore whether miR-3940-5p affects Aβ production, SH-SY5Y APPswe cells overexpressing the Swedish mutant type of APP were transiently transfected with miR-3940-5p mimics, and the expression level of Aβ was detected using ELISA. The results are as follows: The dual-luciferase reporter assays validated the targeting specificity of miR-3940-5p for PSEN1. Overexpression of miR-3940-5p significantly reduced the mRNA and protein levels of PSEN1 in SH-SY5Y cells. Conversely, inhibition of miR-3940-5p led to an increase in PSEN1 mRNA levels. Transfection of miR-3940-5p mimics into SH-SY5Y-APPswe cells resulted in a significant reduction in Aβ42 and Aβ40. Lentiviral-mediated overexpression of miR-3940-5p significantly decreased the expression of PSEN1 and did not significantly affect the expression of other predicted target genes. Furthermore, stable overexpression of miR-3940-5p in SH-SY5Y-APPswe cells mediated by lentivirus significantly reduced the expression of PSEN1 and the production of Aβ42 and Aβ40. Therefore, our study demonstrates for the first time the functional importance of miR-3940-5p in antagonizing Aβ production through specific and direct targeting of PSEN1.